Congenital fusion of jaw and ankyloblepharon filiforme adnatum: Malformation and multiple systems anomaly - Mallika P Reddy; SR Raghu (Indian Journal of Plastic Surgery)
Congenital fusion of jaw and its association with ankyloblepharon filiforme adnatum is reported but is a quite rare congenital benign anomaly. It may be unilateral or bilateral and can present with a single system or multiple systems involvement. This report concentrates on describing the clinical features of above disease, likely aetiological causes, and embryogenesis with classification, diagnostic, and, treatment modality, anesthesia problems and review of literature.